2008
DOI: 10.1037/0022-006x.76.2.347
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of peer-led eating disorders prevention: A replication trial.

Abstract: The aim of this study was to replicate and extend results of a previous trial that investigated the effectiveness of 2 peer-led eating disorders prevention interventions in reducing eating disorder risk factors in undergraduate women (C. B. Becker, L. M. Smith, & A. C. Ciao, 2006). To extend findings from the previous study by allowing for investigation of differential response, the authors randomly assigned a larger sample of both higher and lower risk sorority members (N ϭ 188; age M ϭ 18.64 years, range ϭ 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
98
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 132 publications
(103 citation statements)
references
References 19 publications
3
98
1
1
Order By: Relevance
“…The primary aim of the study was to examine outcome differences between a two-session version and a four-session version of the dissonance intervention, both of which effectively reduce ED risk factors (Becker et al, 2008; 2006; 2005; Stice et al, 2001; 2006; 2000; 2008 Stice et al, 2002). This study was guided by evidence that distributing prevention content across a greater number of sessions facilitates learning, consolidation, skills practice, and behavior change (Bouton, 2000, 2002) and by important clinical considerations such as increasing retention and enhancing group cohesion, which may be achieved by consolidating intervention content which reduces logistical scheduling difficulties.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary aim of the study was to examine outcome differences between a two-session version and a four-session version of the dissonance intervention, both of which effectively reduce ED risk factors (Becker et al, 2008; 2006; 2005; Stice et al, 2001; 2006; 2000; 2008 Stice et al, 2002). This study was guided by evidence that distributing prevention content across a greater number of sessions facilitates learning, consolidation, skills practice, and behavior change (Bouton, 2000, 2002) and by important clinical considerations such as increasing retention and enhancing group cohesion, which may be achieved by consolidating intervention content which reduces logistical scheduling difficulties.…”
Section: Methodsmentioning
confidence: 99%
“…Some of the most efficacious prevention programs have been informed by the dual-pathway model of bulimic pathology, which posits five risk factors for the development of bulimia nervosa: social pressure to be thin, thin ideal internalization, body dissatisfaction, dieting, and negative affect (Stice, 2001; Stice & Agras, 1998). Dissonance-based programs primarily target internalization of the thin ideal and have demonstrated both efficacy and effectiveness (Becker, Bull, Schaumberg, Cauble, & Franco, 2008; Becker, Smith & Ciao, 2006; Stice, Chase, Stormer, & Appel, 2001; Stice, Mazotti, Weibel, & Agras, 2000; Stice, Shaw, Burton, & Wade, 2006; Stice, Marti, Spoor, Presnell, & Shaw, 2008; Stice, Trost, & Chase, 2003). However, there is room for improvement.…”
mentioning
confidence: 99%
“…CD also has proven effective in mixed risk populations. Becker and colleagues also have demonstrated via a series of studies that CD reduces ED pathology (typically measured via the diagnostic items of the Eating Disorder Examination-Questionnaire) when delivered to collegiate women who had not been selected because of body dissatisfaction (Becker, Smith, & Ciao, 2005;Becker, Smith, & Ciao, 2006;Becker, Bull, Schaumberg, Cauble, & Franco, 2008;Perez, Becker, & Ramirez, in press). This is important because many social systems prefer to deliver programs more universally as opposed to selecting (and possibly stigmatizing) high risk individuals.…”
Section: Is One Of Very Few Ed Prevention Programs To Meet the Amementioning
confidence: 99%
“…This is important because many social systems prefer to deliver programs more universally as opposed to selecting (and possibly stigmatizing) high risk individuals. Becker and colleagues also demonstrated that undergraduate students could be trained to effectively lead CD to their mixed risk peers (Becker et al, 2006;Becker, Bull, Schaumberg et al, 2008).…”
Section: Is One Of Very Few Ed Prevention Programs To Meet the Amementioning
confidence: 99%
See 1 more Smart Citation